PAVEL FLORENCE'S APPROACH TO THE MAIN COGNITIVE AND LINGUISTIC CATEGORIES (Heritage, 2022)
In this paper we try to discover how a Russian philosopher Pavel Florensky defines and analyses the nature of words, sentences and concepts in order to represent the mechanism of human thinking. He accentuates the relation between individual and collective experience that both participate in the creation of concepts. We show that in his view word semantics is dynamic phenomenon because its basic features are determined by general meanings that we acquire through Language but that we expand and modify them through our personal perception of reality. Florensky insists on the role of context in the interpretation of lexemes and states that this contributes to the economy and creativity of Language. We  also explain the difference between what he calls spiritual and verbal communication. Finally, we compare the ideas of this philosopher with the findings of modern linguistic and cognitive theories and demonstrate to which extent they converge (and prove that he scientifically was ahead of his time) and to which extent they are specific and non-transparent, because they are marked by his theological approach to human beings and their most important gift – the faculty of language.
Keywords: Pavel Florensky, words, sentence, mind, Theological approach, perception of reality